Tonal Processes in Ǹko ̩̀ ro ̩́ o ̩̀ (Kirika) - Ebitare F. Obikudo (Genius Journals, 2024)
About sixty to seventy percent of the world’s languages are tonal. The majority of African languages are either tonal or tonal-accent languages. The most outstanding characteristic of tones in African languages is their independence with respect to their tone bearing units. Just as tone bearing units or speech sound segments are modified in certain definable environments, tones are also modified in certain phonetic environments giving rise to tonal processes. This paper discusses seven tonal processes that are evident in Ǹ ko̩ ro̩ o̩ , an Eastern I̩jo̩ language belonging to the Niger-Congo phylum. Nko̩ ro̩ o̩ is a register tone language having high and low tones in addition to a downstepped high tone. The tonal processes include tone stability, tone elision, tone assimilation, tone dissimilation, tone copying, tone replacement, and tone metathesis. The autosegmental phonology theory that treats tones as autonomous segments was employed to provide a graphic illustration of the tonal processes. The major findings reveal that tone stability results in floating low tones and syllabic nasals, tone elision give rise to an unusual CRV syllable structure, and tonal processes are instrumental to the construction of various grammatical units such as nominal constructions, verb inflections, imperative verb forms, reduplicants, and coordinating conjunctions. The paper concludes that tonal processes in Nko̩ ro̩ o̩ are conditioned by both the phonetic environment and grammatical constraints.
Keywords: Nko̩; I̩jo̩; tonal processes; tone stability